Parametric Evaluation of Strength of Fiber/Epoxy Composites - Yüncüoğlu, Ercüment; İnce, Serdar Turgut (Fırat University, 2021)
Fiber/epoxy composites are widely used in engineering structures due to their durability and lightness. How the strength of the material changes in various situations such as the fiber type, the number of layers, the angle it will be subjected to loading, the loading speed is important for the designers to choose the composite material. In this study, a full factorial experimental design was established in the light of these parameters and the cross effects of the parameters on each other were evaluated in terms of failure stress, strain and absorbed energy, and useful results and observations were obtained for designers.

Mühendislik yapılarında fiber/epoksi kompozitler dayanıklılık ve hafifliği nedeniyle yaygınca kullanılmaktadır. Tasarımcılar açısından kompozit malzemenin seçimi için fiber tipi, katman sayısı, yüklemeye maruz kalacağı açı, yükleme hızı gibi çeşitli durumlarda malzemenin mukavemetinin nasıl değiştiği önemlidir. Bu çalışmada bu parametreler ışığında tam faktöriyel bir deney tasarımı kurulmuş ve parametrelerin birbirleri üzerindeki çapraz etkileri gerilme, gerinim ve emilen edilen enerji açısından değerlendirilerek tasarımcılar için kullanışlı sonuçlar ve gözlemler elde edilmiştir.
Farklı Parametreler Işığında Fiber Epoksi Tabakalı Kompozitlerin Mukavemet Özelliklerinin Deneysel Olarak Değerlendirilmesi